Pelatihan Canva Untuk Media Pembelajaran Audio Visual Guru SMK Negeri 1 Rambah Samo - Muslim; Detri Amelia Chandra; Ari Aprilia Dwiana; Sri Wahyudi; Firman Santosa; Ridwan (STMIK Royal, 2026)
Abstract: The rapid development of digital technology has encouraged teachers to adapt learning practices through the use of innovative and engaging instructional media. However, many teachers still experience limitations in developing audio-visual learning media that are pedagogically appropriate and easy to produce. This community service activity aimed to improve teachers’ digital competence in developing audio-visual learning media using Canva at SMK Negeri 1 Rambah Samo. The activity was conducted from August to December 2025 through a training and mentoring approach. The implementation stages consisted of needs identification, material delivery, demonstration, guided practice, product review, and evaluation. Evaluation was carried out through pre-test and post-test questionnaires, observation of participants’ practice, and assessment of the learning media products developed by teachers. The results showed an increase in teachers’ understanding from 46% before the training to 84% after the training, indicating an improvement of 38%. In addition, 88% of participants were able to produce audio-visual learning media adapted to their respective subjects. The training also encouraged collaboration among teachers and increased their confidence in applying digital media in classroom instruction. This program demonstrates that practical and continuous Canva-based training can support teachers in creating more interactive, relevant, and meaningful learning experiences in vocational schools. Keywords: canva; audio visual; teacher training; digital competence; learning media. Abstrak: Perkembangan teknologi digital menuntut guru untuk mampu menghadirkan pembelajaran yang lebih inovatif melalui pemanfaatan media pembelajaran yang menarik dan relevan. Namun, masih banyak guru yang menghadapi keterbatasan dalam mengembangkan media pembelajaran audio visual yang mudah dibuat dan sesuai dengan kebutuhan pedagogis. Kegiatan pengabdian kepada masyarakat ini bertujuan meningkatkan kompetensi digital guru dalam membuat media pembelajaran audio visual berbasis Canva di SMK Negeri 1 Rambah Samo. Kegiatan dilaksanakan pada Agustus sampai Desember 2025 melalui pendekatan pelatihan dan pendampingan. Tahapan kegiatan mencakup identifikasi kebutuhan, penyampaian materi, demonstrasi, praktik terbimbing, review produk, dan evaluasi. Evaluasi dilakukan melalui angket pre-test dan post-test, observasi praktik, serta penilaian produk media pembelajaran yang dihasilkan peserta. Hasil kegiatan menunjukkan adanya peningkatan pemahaman guru dari 46% sebelum pelatihan menjadi 84% setelah pelatihan, dengan peningkatan sebesar 38%. Selain itu, sebanyak 88% peserta berhasil menghasilkan media pembelajaran audio visual sesuai dengan mata pelajaran masing-masing. Kegiatan ini juga mendorong kolaborasi antarguru dan meningkatkan kepercayaan diri dalam menerapkan media digital di kelas. Dengan demikian, pelatihan berbasis praktik dan pendampingan terbukti efektif dalam mendukung inovasi pembelajaran dan penguatan kompetensi digital guru di sekolah kejuruan. Kata kunci: canva; media audio visual; pelatihan guru; kompetensi digital; pembelajaran.